2023
DOI: 10.3389/fnut.2023.1039965
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and antioxidant activity of wild edible fruits of the eastern Himalaya, India

Abstract: The eastern Himalayas, one of the important hotspots of global biodiversity, have a rich diversity of wild edible fruit trees. The fruits of these tree species have been consumed by the tribal people since time immemorial. However, there is limited information available on the biochemical and antioxidant properties of the fruits. Therefore, the present investigation was undertaken to study the physico-chemical and antioxidant properties of the nine most important wild fruit trees. Among the species, Pyrus pash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Given agricultural technologies, there is potential for the domestication of some species of wild fruits that can be adapted to local environments, including those on the verge of going extinct. For the most part, understanding the phytochemical properties of the wild fruit species could provide better pathways to safe use [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given agricultural technologies, there is potential for the domestication of some species of wild fruits that can be adapted to local environments, including those on the verge of going extinct. For the most part, understanding the phytochemical properties of the wild fruit species could provide better pathways to safe use [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing humans with vital nutrients such as carbohydrates, dietary fiber, and protein, these wild fruits also include minerals and phytochemicals that are good for your health [ 2 ]. Due to their high fiber and antioxidant content, recent studies have revealed that wild fruits can treat a variety of illnesses, including diabetes, cardiovascular problems, inflammations, and disorders of the digestive and urinary tract [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since, Türkiye is the homeland of red raspberries, there is many suitable areas for raspberry cultivation. Today, its cultivation has gained importance in large enterprises, family businesses and as an intermediate production option [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%